Illnessand Treatment in Theological and Normative Viewpoints - Nabilla Andasari Putri; Ulfi Nurhida Mahardika; Eka Intan Kusuma Wardhani; Marina Ayu Ningtyas; Tri Oktarina; Muthoifin; Qoree Butlam; Muhammad Hamma’Adama Ahmad; Mohammed Akhiruddin Ibrahim (Walidem Institute and Publishing, 2024)
Vol.1, No.3, 2023, pp. 163-172